2021
DOI: 10.3389/fped.2021.743639
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Etiology Diagnosis of Fetal Growth Restriction Using Single-Nucleotide Polymorphism-Based Chromosomal Microarray Analysis

Abstract: Background: An increase in pathogenic copy number variants (pCNVs) has been recognized to associate with fetal growth restriction (FGR). Here, we aim to explore the application value of chromosomal microarray analysis (CMA) in prenatal diagnosis of FGR.Methods: Prenatal ultrasound was applied to identify FGR. A total of 149 pregnant women with FGR were enrolled in our study. All subjects underwent karyotype analysis and CMA to reveal the chromosomal abnormalities.Results: In this study, all subjects were succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…6 The most common chromosomal numerical abnormalities associated with FGR were triploid (69,XXX and 69,XXY) and trisomy 18, 21, and 13. 6,7 Trisomy 18 was identified in over 50% of chromosomal numerical abnormalities in severe FGR, defined as AC 3 rd percentile for GA. 8 For FGR associated with fetal structural abnormalities (FGR defined as AC < 5 th percentile for GA), the detection rate of fetal aneuploidy was 21% (4/19), while for isolated FGR diagnosed before 24 weeks of gestational age, the detection rate of fetal aneuploidy was 20% (3/15). 9 Despite the heterogeneity in definitions for FGR, the studies above all indicated that amniocentesis with karyotyping should be offered to rule out chromosomal abnormalities for FGR with fetal structural anomalies, severe FGR defined as AC 3 rd percentile for GA or earlyonset FGR diagnosed before 24 weeks gestational age even if isolated.…”
Section: Fetal Chromosomal Abnormalitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…6 The most common chromosomal numerical abnormalities associated with FGR were triploid (69,XXX and 69,XXY) and trisomy 18, 21, and 13. 6,7 Trisomy 18 was identified in over 50% of chromosomal numerical abnormalities in severe FGR, defined as AC 3 rd percentile for GA. 8 For FGR associated with fetal structural abnormalities (FGR defined as AC < 5 th percentile for GA), the detection rate of fetal aneuploidy was 21% (4/19), while for isolated FGR diagnosed before 24 weeks of gestational age, the detection rate of fetal aneuploidy was 20% (3/15). 9 Despite the heterogeneity in definitions for FGR, the studies above all indicated that amniocentesis with karyotyping should be offered to rule out chromosomal abnormalities for FGR with fetal structural anomalies, severe FGR defined as AC 3 rd percentile for GA or earlyonset FGR diagnosed before 24 weeks gestational age even if isolated.…”
Section: Fetal Chromosomal Abnormalitiesmentioning
confidence: 99%
“…The detection rate of diagnostic CNVs was significantly different among three FGR groups; 33.33% for the FGR with fetal structural anomalies group; 8.77% FGR with soft markers and without structural anomalies group; and 8.06% isolated FGR group. 7 A recent retrospective study from 13 fetal medicine centers including 146 fetuses diagnosed with isolated FGR (defined as EFW < 10 th percentile for GA), demonstrated that the total genetic anomalies identified by CMA were 7.5% (11/146); furthermore, CMA provided an incremental diagnostic rate of 3.4% (5/146) compared with karyotype analysis, with the detection of duplication at 16p12.2 and deletions at 19q12q13.12, 12q13.13, and 19p13.2p13.11. 14 Another study analyzed 133 fetuses with FGR (defined as EFW < 3 th percentile for GA) before 32 weeks of gestation and showed that the incremented yield of the diagnostic CNVs by CMA compared with karyotyping was 10.5% for FGR with fetal structural abnormalities, 10.0% for FGR with soft markers and without structural anomalies, and 4.8% for isolated FGR.…”
Section: Fetal Chromosomal Abnormalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research focused on diagnosis, intrauterine monitoring, treatment, and prognosis of fetuses with FGR; however, currently there are only a few studies on the genetic etiology of FGR. Genetic factors that cause FGR have rarely been reported, and some studies that reported a genetic association were conducted with small sample sizes [ 5 ]. Single-nucleotide polymorphism array (SNP-array) can detect copy number variations (CNVs) at a genome-wide level, as well as chimeras (> 30%), loss of heterozygosity, and uniparental disomy (UPD) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Base mismatch in DNA molecules easily causes gene mutations, especially point mutations, which are often an important cause of hereditary and genetic predisposition diseases [ 1 ]. In recent years, the detection and analysis of gene mutations have become a topic of increasing interest, such as pathogenic gene screening and prenatal diagnosis, which can provide the basis for early diagnosis and precise treatment of diseases [ 2 ]. At present, many methods are in place for detecting gene mutations, such as whole-genome sequencing, but they still have certain limitations in terms of experimental cost, sensitivity, and accuracy.…”
Section: Introductionmentioning
confidence: 99%